Imposed Cold-water Ingestion during Open Water Swimming in Internationally Ranked Swimmers - Hue, O.; Monjo, R.; Riera, F. (International Journal of Sports Medicine, 2015)
The authors explored the effects of open water swimming in a tropical environment on both core temperature (Tc) and thermal perceptions of high-level swimmers during an official international 10-km race and two 5-km swimming tests. The swimmers drank neutral water (i. e., 28.0±3.0°C) ad libitum every 2 000 m during Competition, whereas the ingested volume was imposed in the 5-km tests: every 1 000 m, they drank 190 mL of cold water (CW, 1.1±0.7°C) or neutral water (NW, 28.0±3.0°C). They also self-rated their thermal comfort and sensation (TC and TS), and their Tc was recorded. The study demonstrated that adequate fluid intake significantly decreased Tc in swimmers swimming at race pace in hot water (i. e., 37.5±0.3°C vs. 38.3±0.4°C, in NW vs. Competition, respectively). This effect was more pronounced with cold water (i. e., 36.7±1.1°C, in CW). No significant changes were noted in mean heart rate (i. e., 145±5, 143±4 and 141±5 bpm for NW, CW and Competition, respectively). Further studies are needed to explore the effect of this cooling method on the performances of international swimmers during tropical swimming events.
Keywords: competition; cooling; core temperature; hydration; tropical climate